2016
DOI: 10.1001/jama.2016.16144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Donor Human Milk Compared With Preterm Formula on Neurodevelopment of Very Low-Birth-Weight Infants at 18 Months

Abstract: IMPORTANCE For many very low-birth-weight (VLBW) infants, there is insufficient mother's milk, and a supplement of pasteurized donor human milk or preterm formula is required. Awareness of the benefits of mother's milk has led to an increase in use of donor milk, despite limited data evaluating its efficacy.OBJECTIVE To determine if nutrient-enriched donor milk compared with formula, as a supplement to mother's milk, reduces neonatal morbidity, supports growth, and improves neurodevelopment in VLBW infants. DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
191
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(222 citation statements)
references
References 40 publications
12
191
4
2
Order By: Relevance
“…Further evidence for the immunoprotective benefits of human milk comes from meta-analyses of randomised controlled trials that assessed the effect of donor human breast milk versus formula for feeding preterm infants [14]. Despite the potential for donor milk processing, including freeze-thaw cycles and pasteurisation, to reduce levels of its bioactive components, recent high-quality trial data have confirmed that feeding very preterm infants with donor breast milk versus formula reduces the risk of NEC [15]. Some concerns remain about the nutritional sufficiency of donor breast milk, but this can be compensated by addition of multi-nutrient fortifiers extracted from cow’s milk [16].…”
Section: Human Milk: the Ultimate Immunonutrientmentioning
confidence: 99%
“…Further evidence for the immunoprotective benefits of human milk comes from meta-analyses of randomised controlled trials that assessed the effect of donor human breast milk versus formula for feeding preterm infants [14]. Despite the potential for donor milk processing, including freeze-thaw cycles and pasteurisation, to reduce levels of its bioactive components, recent high-quality trial data have confirmed that feeding very preterm infants with donor breast milk versus formula reduces the risk of NEC [15]. Some concerns remain about the nutritional sufficiency of donor breast milk, but this can be compensated by addition of multi-nutrient fortifiers extracted from cow’s milk [16].…”
Section: Human Milk: the Ultimate Immunonutrientmentioning
confidence: 99%
“…In this cohort, there was no difference in the incidence of BPD between infants who received human milk and those who did not, but the investigators did not evaluate a dose dependent relationship for this morbidity. Similarly, in the recent Canadian randomised trial of donor human milk versus preterm formula as a supplement to mother’s own milk, O’Connor and colleagues8 found no significant difference in the number of infants receiving supplemental oxygen at 36 weeks PMA, although it is important to note that infants in both groups received a substantial proportion of maternal milk in this study. The report by Patel does not address the question of the impact of donor human milk on BPD.…”
mentioning
confidence: 46%
“…A diferencia de otros artículos (14), nosotros encontramos mayor peso a los dos años en los niños alimentados con lactancia materna exclusiva. Es conocido el superior valor nutricional de la leche de la propia madre comparada con la leche donada, dado que esta suele proceder de madres que han dado a luz niños a término y con lactancia establecida.…”
Section: Discussionunclassified